2020
DOI: 10.3389/fcimb.2020.00001
|View full text |Cite
|
Sign up to set email alerts
|

New Insights Into CRASP-Mediated Complement Evasion in the Lyme Disease Enzootic Cycle

Abstract: Lyme disease (LD), which is caused by genospecies of the Borrelia burgdorferi sensu lato complex, is the most common vector-borne disease in the Northern hemisphere. Spirochetes are transmitted by Ixodes ticks and maintained in diverse vertebrate animal hosts. Following tick bite, spirochetes initially establish a localized infection in the skin. However, they may also disseminate hematogenously to several distal sites, including heart, joints, or the CNS. Because they need to survive in diverse microenvironme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
102
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(107 citation statements)
references
References 79 publications
5
102
0
Order By: Relevance
“…A similar result has been reported by Abdollahi et al 19 This variation from Chinese and Iranian studies may be explained on genetic clustering of susceptible loci which may vary among different ethnicities. 20 Another reason for the contradictory findings as compared to Zhao et al 9 , Li et al 17 and Fan et al 18 may be the homogenous sample of Chinese ethnicity in their studies.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…A similar result has been reported by Abdollahi et al 19 This variation from Chinese and Iranian studies may be explained on genetic clustering of susceptible loci which may vary among different ethnicities. 20 Another reason for the contradictory findings as compared to Zhao et al 9 , Li et al 17 and Fan et al 18 may be the homogenous sample of Chinese ethnicity in their studies.…”
Section: Discussionmentioning
confidence: 88%
“…Al 16 arrived at a similar conclusion when they analyzed published data relying on the status of Anti-A antibody. Zhao et al 9 , Li et al 17 and Fan et al 18 have reported equal representation of blood type-B in COVID-19 and control groups in their studies from Wuhan, China. A similar result has been reported by Abdollahi et al 19 This variation from Chinese and Iranian studies may be explained on genetic clustering of susceptible loci which may vary among different ethnicities.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Such overlap of phenotype indicates a possibility that these proteins have similar or connected functions. This hypothesis is even furthered by the fact that, due to high genetic recombination rate, the functions of Borrelia OSPs often tend to overlap [ 7 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that serological diagnosis is the most appropriate approach to be used in endemic regions, since it is easy to use, non-invasive and rapidly generates results. However, despite the many choices available to be used in the field, no test so far is efficient enough to be used to diagnose the disease in both humans and dogs [6][7][8][9]. Among the serological methods currently used (DAT, IFAT, ELISA and immunochromatographic 40/2012 -Research in Neglected Diseases) (404259/2012-0).…”
Section: Introductionmentioning
confidence: 99%